Night running : how James escaped with the help of his faithful dog : based on a ture story - Carbone, Elisa (Alfred A. Knopf, 2008)
A runaway slave makes a daring escape to freedom with the help of his faithful hunting dog, Zeus. Based on the true story of James Smith's journey from Virginia to Ohio in the mid-1800s.